Emotion Recognition and Adverse Childhood Experiences in Individuals at Clinical High Risk of Psychosis. (21st February 2020) - Tognin, Stefania; Catalan, Ana; Modinos, Gemma; Kempton, Matthew J; Bilbao, Amaia; Nelson, Barnaby; Pantelis, Christos; Riecher-Rössler, Anita; Bressan, Rodrigo; Barrantes-Vidal, Neus; Krebs, Marie-Odile; Nordentoft, Merete; et al.
Abstract: Objective: To investigate the association between facial affect recognition (FAR) and type of adverse childhood experiences (ACEs) in a sample of clinical high risk (CHR) individuals and a matched sample of healthy controls (HCs). Methods: In total, 309 CHR individuals and 51 HC were recruited as part of an European Union-funded multicenter study (EU-GEI) and included in this work. During a 2-year follow-up period, 65 CHR participants made a transition to psychosis (CHR-T) and 279 did not (CHR-NT). FAR ability was measured using a computerized version of the Degraded Facial Affect Recognition (DFAR) task. ACEs were measured using the Childhood Experience of Care and Abuse Questionnaire, the Childhood Trauma Questionnaire, and the Bullying Questionnaire. Generalized regression models were used to investigate the relationship between ACE and FAR. Logistic regressions were used to investigate the relationship between FAR and psychotic transition. Results: In CHR individuals, having experienced emotional abuse was associated with decreased total and neutral DFAR scores. CHR individuals who had experienced bullying performed better in the total DFAR and in the frightened condition. In HC and CHR, having experienced the death of a parent during childhood was associated with lower DFAR total score and lower neutral DFAR score, respectively. Analyses revealed a modest increase of transition risk with increasing mistakes from happy to angry faces. Conclusions: Adverse experiences in childhood seem to have a significant impact on emotional processing in adult life. This information could be helpful in a therapeutic setting where both difficulties in social interactions and adverse experiences are often addressed.